2020
DOI: 10.1101/2020.04.22.053223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ontogeny and function of the circadian clock in intestinal organoids

Abstract: Circadian rhythms regulate diverse aspects of gastrointestinal physiology ranging from the composition of microbiota to motility. However, development of the intestinal circadian clock and detailed molecular mechanisms regulating circadian physiology of the intestine remain largely unknown. The lack of appropriate human model systems that enable organ-and/or diseasespecific interrogation of clock functions is a major obstacle hindering advancements of translational applications using chronotherapy. In this rep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
(96 reference statements)
0
4
0
Order By: Relevance
“… The recent methodological advances have realized self‐organizing 3D culture systems that are histologically similar to a variety of human organs. Rosselot et al (2021) report that mature organoids possess circadian clocks and are susceptible to time‐controlled dosing of drugs. …”
Section: Figure Tissue‐level Oscillations Of Gene Expression and Drug...mentioning
confidence: 99%
See 1 more Smart Citation
“… The recent methodological advances have realized self‐organizing 3D culture systems that are histologically similar to a variety of human organs. Rosselot et al (2021) report that mature organoids possess circadian clocks and are susceptible to time‐controlled dosing of drugs. …”
Section: Figure Tissue‐level Oscillations Of Gene Expression and Drug...mentioning
confidence: 99%
“…One breakthrough recently occurred in this question. The current study by Rosselot et al (2021) constitutes a breakthrough, as it investigated the circadian clock in several types of artificially induced, multicellular structures that mimic the intestinal organ. The authors generated organoids that were different in terms of their maturity, cell origin, or induction process and reported that human intestinal organoids (HIO) induced from the pluripotent stem cells did not show circadian rhythm.…”
Section: Figure Tissue‐level Oscillations Of Gene Expression and Drug...mentioning
confidence: 99%
“…Current studies often rely on the use of in vivo animal models -namely hamster and mouse models [8,9]. They are particularly used when studying immunological aspects of C. difficile; however, immune responses vary greatly between species and disease progression in these models is often dissimilar to that in humans [10]. Further limitations include the differences in anatomy and microbiota composition [11], plus there is a general need to reduce and refine the use of animals in research.…”
Section: Introductionmentioning
confidence: 99%
“…The greater representation of females among human studies could be related to Institutional Review Board approval and participant recruitment. In any case, recent work on organoids and diurnal rodents may lead to more species and tissue diversity in circadian data sets (Rosselot et al, 2022; Bano-Otalora et al, 2021).…”
mentioning
confidence: 99%